Change of Mechanical Properties of Polyethylene Film Materials during Their Modification by Technological Applications and during Aging - Domantsevich, N. I.; Yatsushyn, B. P. (Physics and Chemistry of Solid State, 2020)
Mechanical tests and studies of the structure of modified polyethylene film materials used as packaging elements of electronic devices have been carried out. The modification provided for the introduction of fillers of various types and technological additives that would facilitate the processing of raw materials and ensure a long service life. The peculiarities of changes in mechanical characteristics depending on the number and type of applications, as well as the course of processes under the influence of external factors are established. The relationship between changes in the structure and mechanical properties of polymeric materials is shown.